Effects of Achievement Goal Orientation Types on Subjective Wellbeing - Putri, Tasya Nafasya; Saleh, Airin Yustikarini (UI Scholars Hub, 2020)
In the midst of increasing academic pressure, the subjective well-being of high school students tends to decline as they undergo the school years. In this regard, measuring subjective well-being in specific contexts is necessary to ensure thorough and accurate information that better represents their situation. For this purpose, the study uses subjective well-being in school, which consists of school satisfaction, positive affect, and negative affect. Out of the variables that correlate to subjective well-being in school, achievement goal orientation needs more attention. Thus, the study examines the effects of each type of goal orientation on subjective well-being in school using a 2 × 2 framework. Based on linear regression analysis, mastery-approach goal, performance-approach goal, and performance-avoidance goal have a significant effect on the subjective well-being of 11thgrade high school students in school. However, the opposite is true for the mastery-avoidance goal. The research supports previous research and provides broad information about achievement goal orientation as described by the 2 × 2 framework.